KEPUASAN KERJA KARYAWAN HOUSEKEEPING DEPARTMENT HOTEL PANGERAN PEKANBARU - Heryx "; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purposed to get know the job satisfaction of housekeeping department’s employees in Pangeran Pekanbaru Hotel based on two factors theory Herzberg, they were motivator and maintenance factors.This research used quantitative descriptive method to analyze the problems. Sample of this research is all of housekeeping department’s employees amount 23 peoples decided by census sampling technique. The datas collected by using observation, interview and questionnaire and using the likert scale to get the interval’s range.According to the result of this research, job satisfaction of housekeeping department’s employees in pangeran pekanbaru hotel was in middle level. Some factors weren’t fulfilled yet. From motivator they are promotion and recognition, from maintenance factors they are co worker, quality and technical support, relations with others and psychological working condition.Key words : job satisfaction, housekeeping, pangeran pekanbaru hotel